MORFOFONEMIK VERBA DALAM BAHASA KERINCI - M.Pd, Eva Fitrianti (RC-INSTITUT, 2018)
This Research is about the morphophonemic  verbs process of Kerinci language which is done with the background of many linguistic problems that have not received attention in Kerinci language and only few of the documentation that has been done on the language of Kerinci. This research is done with awareness of the effort to conserve one of the elements of culture, namely language.This research is a qualitative research method with descriptive approach. Descriptive approach aims to describe Kerinci language empirically based on the situation or facts that exist in the field and presented with what it is. The informant is a native speaker of Kerinci. Data collection techniques used are recording techniques, elasticity techniques, and techniques of listening. Data analysis technique used in this research is transcribing data into writing language, translating data into Indonesian, and analyzing data. To facilitate the analysis, the data are already written and translated into Indonesian language, then classified by word category. The result of this research is four rules of morphophonemic process of verb forming affix, ie maN-, N-, bar-, and ta-. The four rules of verb-forming merbophonemic in Kerinci, can be more classified into two processes, namely the process of phoneme change and phoneme removal process.